2011
DOI: 10.4103/0976-500x.83278
|View full text |Cite
|
Sign up to set email alerts
|

Rabeprazole and esomeprazole in mild-to-moderate erosive gastroesophageal reflux disease: A comparative study of efficacy and safety

Abstract: Objective:To compare the efficacy and safety of rabeprazole and esomeprazole in mild-to-moderate erosive gastroesophageal reflux disease (GERD).Materials and Methods:A randomized, single-blinded, outdoor-based clinical study was conducted on 60 patients of mild-to-moderate erosive GERD. After baseline clinical assessment and investigations, rabeprazole (40 mg) was prescribed to 30 patients and esomeprazole (40 mg) to another 30 patients for 4 weeks. The efficacy variables were change in GERD symptom scoring, e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 36 publications
0
3
0
Order By: Relevance
“…Another randomized clinical trial concluded that rabeprazole 20 mg is non-inferior to esomeprazole 20 mg in treating heartburn and regurgitation symptoms in GERD symptoms [18]. However, a randomized single-blinded study reported that rabeprazole 40 mg has better efficacy when compared to esomeprazole 40 mg in mild-to-moderate GERD patients [19]. These findings underscore a favourable aspect of rabeprazole 20 mg as a treatment option for GERD, as it appears to provide symptom relief without causing additional disruptions in stomach function or hormone levels.…”
Section: Discussionmentioning
confidence: 99%
“…Another randomized clinical trial concluded that rabeprazole 20 mg is non-inferior to esomeprazole 20 mg in treating heartburn and regurgitation symptoms in GERD symptoms [18]. However, a randomized single-blinded study reported that rabeprazole 40 mg has better efficacy when compared to esomeprazole 40 mg in mild-to-moderate GERD patients [19]. These findings underscore a favourable aspect of rabeprazole 20 mg as a treatment option for GERD, as it appears to provide symptom relief without causing additional disruptions in stomach function or hormone levels.…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, a randomized clinical trial concluded that rabeprazole 20 mg was non-inferior to esomeprazole 20 mg in treating heartburn and regurgitation symptoms in GERD patients [18]. However, a randomized single-blinded study reported that rabeprazole 40 mg has better efficacy when compared to esomeprazole 40 mg in mild-to-moderate GERD patients [19].…”
Section: Discussionmentioning
confidence: 99%
“…The selected doses are known to be therapeutically effective and safe in adults (15) and adolescents (16), and the highest dose used in this study did not exceed the maximum labeled adult dose (20‐mg dose). Dose selection was based on earlier studies that demonstrated that the known target range for plasma level of exposure (area under the curve, AUC) of rabeprazole for therapeutic acid suppression in adults and adolescents treated with 10‐ and 20‐mg rabeprazole was 400 to 800 ng · h −1 · L −1 (17).…”
Section: Methodsmentioning
confidence: 99%